Deletion of the von Hippel-Lindau gene in pancreatic beta cells impairs glucose homeostasis in mice. - Cantley, J; Selman, C; Shukla, D; Abramov, A; Forstreuter, F; Esteban, M; Claret, M; Lingard, S; Clements, M; Harten, S; Asare-Anane, H; Batterham, R; et al. (2009)
Defective insulin secretion in response to glucose is an important component of the beta cell dysfunction seen in type 2 diabetes. As mitochondrial oxidative phosphorylation plays a key role in glucose-stimulated insulin secretion (GSIS), oxygen-sensing pathways may modulate insulin release. The von Hippel-Lindau (VHL) protein controls the degradation of hypoxia-inducible factor (HIF) to coordinate cellular and organismal responses to altered oxygenation. To determine the role of this pathway in controlling glucose-stimulated insulin release from pancreatic beta cells, we generated mice lacking Vhl in pancreatic beta cells (betaVhlKO mice) and mice lacking Vhl in the pancreas (PVhlKO mice). Both mouse strains developed glucose intolerance with impaired insulin secretion. Furthermore, deletion of Vhl in beta cells or the pancreas altered expression of genes involved in beta cell function, including those involved in glucose transport and glycolysis, and isolated betaVhlKO and PVhlKO islets displayed impaired glucose uptake and defective glucose metabolism. The abnormal glucose homeostasis was dependent on upregulation of Hif-1alpha expression, and deletion of Hif1a in Vhl-deficient beta cells restored GSIS. Consistent with this, expression of activated Hif-1alpha in a mouse beta cell line impaired GSIS. These data suggest that VHL/HIF oxygen-sensing mechanisms play a critical role in glucose homeostasis and that activation of this pathway in response to decreased islet oxygenation may contribute to beta cell dysfunction.